Proteção vacinal por Leishmania infantum com o uso da proteína de ligação guanosina -5'- trifosfato (GTP) recombinante associada à micelas poliméricas á base de poloxamer 407 - Flávia Prata Linhares (2022)
Leishmaniases are endemic diseases in 98 countries worldwide, with over 1 billion people at risk of infection by the Leishmania parasite. They can be divided into two main groups according to clinical manifestations: tegumentary leishmaniasis (TL) and visceral leishmaniasis (VL). Although they have a worldwide incidence, leishmaniasis are neglected diseases and there are no effective control measures against them. Thus, the development of prophylactic vaccines capable of inducing protective immunity against infection by the parasite could be considered as a measure of control against the spread of the disease. In this work, a Leishmania parasite protein called guanosine 5'-triphosphate (GTP) protein, which was identified in a previous immunoproteomic study developed by the group, was evaluated as vaccine candidate in BALB/c mice against Leishmania infantum infection. The protein was used in the recombinant version (rGTP) and it was associated with saponin (Sap) or in polymeric micelles (Mic) as adjuvants. Results showed that both rGTP/Sap and rGTP/Mic compositions induced a Th1-type immune response in the vaccinated animals, with significantly elevated levels of IFNγ, IL-12, IL-2, TNF-α, GM-CSF, nitrite, in addition to IgG2a isotype antibodies and positive lymphoproliferation; when compared to data found in the control groups (saline, saponin and empty micelles). The immune response before and after infection was accompanied by a significantly lower parasite load found in animals vaccinated with rGTP/Sap and rGTP/Mic; when their spleens, livers, bone marrows and draining lymph nodes were evaluated. Results showed that rGTP/Mic immunization induced a more polarized Th1-type response and a higher reduction in organic parasitism, when compared to the other groups. In conclusion, rGTP showed satisfactory results in inducing protection against murine VL and could be considered as a candidate to be evaluated in future studies in other mammalian models.